Does an Improvement in Competency Lead to Enhanced Employee Performance? - Mukhlis, Dadang; Suryaman, Warman; Kurhayadi (Bulletin of Management and Business, 2023)
The purpose of this research is to analyze the influence of competence on employee performance at the Public Works and Spatial Planning Agency of Cimahi City. The research method employed is a survey method, and the study is characterized as a descriptive correlational research. The population for this study comprises the employees of the Public Works and Spatial Planning Agency of Cimahi City. Sample selection in this research uses a saturated sampling technique (census), resulting in a sample size of 42 individuals. Data analysis is conducted using descriptive analysis and simple linear regression analysis with the assistance of SPSS data processing tool. The research findings indicate that competence has a significant influence on employee performance at the Public Works and Spatial Planning Agency of Cimahi City. The extent of influence of the competence variable on employee performance is 70.3%, while the remaining 29.7% is influenced by other factors.